Pengaruh Pertumbuhan Penduduk, Tingkat Pengangguran, Inflasi dan Indeks Pembangunan Manusia terhadap Tingkat Kemiskinan di Provinsi Jambi - M. Iqbal Rizki Aufa; Amril Amril; Yohanes Vyn Amzar (Jurnal Ekonomi Aktual, 2022)
This study aims to analyze the effect of population growth, inflation, unemployment rate, and the Human Development Index on the poverty rate in Jambi Province. The data used is secondary data for the 2001 – 2018 period. The data comes from the Central Bureau of Statistics for Jambi Province. Data were analyzed descriptively and using multiple linear regression models. The analysis research results found that population growth and inflation positively and significantly affected poverty. On the other hand, the unemployment rate and the Human Development Index have no significant effect on the poverty rate.